New Occurrence of Nigrospora oryzae Causing Leaf Blight in Ginkgo biloba in China and Biocontrol Screening of Endophytic Bacteria - Yuan Tao; Chun Yang; Sinong Yu; Fangfang Fu; Tingting Dai (Microorganisms)
Ginkgo biloba is a multifunctional composite tree species that has important ornamental, economic, medicinal, and scientific research value. In October 2023, the foliage of G. biloba on the campus of Nanjing Forestry University exhibited leaf blight. Black-brown necrotic spots were observed on a large number of leaves, with a disease incidence of 86%. After isolating a fungus from symptomatic leaves, pathogenicity was tested to satisfy Koch’s postulates. Using morphological features and multi-gene phylogenetic analyses of an internal transcribed spacer (ITS), elongation factor 1-alpha (EF1-α), and beta-tubulin (β-tub), the isolates YKB1-1 and YKB1-2 were identified as Nigrospora oryzae. N. oryzae was previously reported as an endophyte of G. biloba. However, this study shows it to be pathogenic to G. biloba, causing leaf spots. Two endophytic bacteria were isolated from asymptomatic leaves of diseased G. biloba trees, and their molecular identification was performed using 16S ribosomal DNA (16S rDNA). GBB1-2 was identified as Bacillus altitudinis, while GBB1-5 was identified as Bacillus amyloliquefaciens. The screening and verification of endophytic bacteria provide a new strategy for the control of N. oryzae.